Design and Finite Element Analysis of Prosthetic Hand Controlled by Wireless Gestures for Differently-abled People. Issue 1 (September 2020) - Shanmugasundar, G; Dharanidharan, M; Vishwa, D; Jayaprakash, A; Abimanyu, P
Abstract: This paper focuses on the design and finite element analysis of the prosthetic hand for differently-able people. The prosthetic hand consists of two sections: one is the transmitting section and another one is the receiving section. The transmitting section consists of a glove embedded with a series of flex sensors connected with a microcontroller and a wi-fi module. The flex sensors are fixed along with each finger which captures and converts the motion of the fingers into analog signals and is transmitted to the receiving section through the wi-fi module. The receiving section consists of the prosthetic hand in which each finger is actuated by the servo motors. The transmitted signals are received by the wi-fi module in the receiver section through the microcontroller and are converted into digital signals. The fingers of the prosthetic hand are actuated by the servo motors corresponding to the received digital signals. The methodology involved in this research is the designing, meshing, and analyzing of a prosthetic hand using the PTC Creo software and then assembling electronic components. The analysis of the prosthetic hand involves the analysis of equivalent stress and total deformation at various regions of the prosthetic hand by selecting steel as a material to fabricate.